Market-Based Fiscal Discipline in Monetary Unions : Evidence From the U.S. Municipal Bond Market - Goldstein, Morris (IMF Working Papers; Working Paper ;, 1991)
The concept of market-based fiscal discipline posits that a government which runs persistent, excessive fiscal deficits will face an increased cost of borrowing and eventually, a reduced availability of credit, and that these market actions will provide an incentive to correct irresponsible fiscal behavior. This paper presents new empirical evidence on market-based fiscal discipline by estimating the relationship between the cost of borrowing and fiscal policy behavior across U.S. states. We find that U.S. states which have followed more prudent fiscal policies are perceived by the market as having lower default risk and are therefore able to reap the benefit of lower borrowing costs.